مقدمة في الكلام على البسملة و الحمدلة - الخطيب الشربيني، محمد بن أحمد الشربيني، ت. 977 هـ.; الصفار، منال صلاح الدين عزيز (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2010)
1-This is acutural message and auseful manuscript which has avaluable scientific in Al Qural science from the tenth century. \ 2- The origin is distinguished by wide cover and aducate and accurate. The reader does \ not have to refer to other references. \ 3- It has a summary which shows scientific views and those who were paraphrasing parsing and the meaning and explanining which related to them about linguistic research and useful clearing.
Keywords: البسملة -- الحمدلة -- الجوانب اللغوية -- الإعراب -- تحقيق النصوص